ANALYSIS OF THE RULES OF PROCESSING THE FIBER OF SHOULDER DRESSES USING MANNEQUIN, MODELING, GRAMMAR PIECES AND PIECE METHOD (British Journal of Global Ecology and Sustainable Development, 2024)
The rules of obtaining shoulder-length clothes by the method of mock-up, layout, gauge pieces and piece method and their practical application.